SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BARANG GADAI NASABAH DIKANTOR PEGADAIAN CABANG SIGLI MENGGUNAKAN METODE FROFILE MATCHING BERBASIS WEB - Sari, Nabila; Husaini, Husaini; Razi, Zulfa (Jurnal Real Riset, 2023)
The Profile Matching method is profile matching, carried out to identify good and bad customers. These customers can be measured using several assessment criteria. In addition, in designing a decision support system, we must determine the feasibility of pawn goods according to the requirements. Therefore, we apply the Profile Matching Method to determine the feasibility of pawning the item. The database used is the MySql database which is stored on an online server so that it can be accessed by web-based system applications.Keywords : Profile Matching Method, Customers, Databases